As intervenções das políticas urbanas na morfologia das construções e sua relação com a sustentabilidade da cidade: estudo de caso no bairro da Mooca - Vitiello, Soraia Cristina Barroso (2018)
This dissertation focuses on the political aspects of the Paulistan Urban Legislation and its relationship with the City's Sustainability, having as a case study the Mooca neighborhood. Divided into four chapters, part of the historical analysis of urban development, showing an overview of the phases of the Industrial Revolution to the Architectural and Urbanistic Styles associated with the discussions on Urban Sustainability and its applications in Urban Policies, especially in the city of São Paulo, in order to establish a diagnosis about relations the Morphology of Buildings, Urban Policies and Sustainable Development.